Perancangan Website E-Commerce Jajak Indonesia - Julianto, Julianto; Dewayani, Ery; Arisandi, Desi (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Jajak Indonesia is a portal of tourism information in Indonesia. Jajak Indonesia itself is a community provides a variety of information about tourism site that are usually less in the know by many people, including Indonesia itself. Features in Jajak Indonesia: tourist destinations, hotels around the tour, events around the tour, tourist news, tourist attractions, tourist events, and tourist blog. This system development aim to added a new feature called Gerai Jajak. An E-Commerce feature site sells for local sellers who live around the tourism site. With this feature is expected to help increase the income of the local sellers, though local product sales. The development method used is the method of SDLC (System Development Life Cycle) and using the PHP as programming language and MySQL for database. The results of the system testing prove all features work properly and can implement